(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Review the clinical and X-ray characteristics of patients with impacted lower wisdom teeth, Parant II and III types at The Air Defence - Air Force Medical Institute in 2023. Method: The study design is a non-controlled, clinical intervention study evaluating results according to a before-after model. Results: We performed lower wisdom tooth extraction surgery according to Parant II and III for 90 patients, the group of patients from 18 - 24, 25 - 30 years old accounted for the highest proportion. Lower jaw wisdom teeth grow in a horizontal position and are deviated near the corner, accounting for the highest rate. There are no lingually deviated wisdom teeth. Lower wisdom teeth in position A2 account for the highest rate. Lower wisdom teeth not adjacent to the alveonar canal account for the highest rate. Teeth with average difficulty (6-10 points) account for the highest rate. Lower jaw wisdom teeth mainly cause complications of periodontitis and distal decay of the lower second molar. The highest level of pain 1 day after tooth extraction is moderate pain. Conclusion: Female patients account for a higher proportion of 52.23%. Mandibular wisdom teeth deviate near the corner and lie horizontally, accounting for the highest rate. Lower wisdom teeth in position A2 account for the highest rate of 42.22%, position B accounts for the second most at 40%. 63.33% of lower wisdom teeth are not adjacent to the lower dental canal, the remaining 36.67% of teeth are not adjacent to the lower dental canal.